Class I and IIa HDACs Mediate HIF‐1α Stability Through PHD2‐Dependent Mechanism, While HDAC6, a Class IIb Member, Promotes HIF‐1α Transcriptional Activity in Nucleus Pulposus Cells of the Intervertebral Disc. (15th March 2016) - Schoepflin, Zachary R; Shapiro, Irving M; Risbud, Makarand V
ABSTRACT: The objective of this study was to determine the role of histone deacetylases (HDACs) in regulating HIF‐1α protein stability and activity in nucleus pulposus (NP) cells. Treatment of NP cells with pan‐HDAC inhibitor TSA resulted in decreased HIF‐1α levels under both normoxia and hypoxia in a dose‐dependent fashion. TSA‐mediated HIF‐1α degradation was rescued by concomitant inhibition of not only the 26S proteasome but also PHD2 function. Moreover, TSA treatment of PHD2 −/− cells had little effect on HIF‐1α levels, supporting the notion that inhibition of PHD2 function by HDACs contributed to HIF‐1α stabilization. Surprisingly, class‐specific HDAC inhibitors did not affect HIF‐1α protein stability, indicating that multiple HDACs controlled HIF‐1α stability by regulating HIF‐1α‐PHD2 interaction in NP cells. Interestingly, lower‐dose TSA that did not affect HIF‐1α stability decreased its activity and target gene expression. Likewise, rescue of TSA‐mediated HIF‐1α protein degradation by blocking proteasomal or PHD activity did not restore HIF‐1 activity, suggesting that HDACs independently regulate HIF‐1α stability and activity. Noteworthy, selective inhibition of HDAC6 and not of class I and IIa HDACs decreased HIF‐1‐mediated transcription under hypoxia to a similar extent as lower‐dose TSA, contrasting the reported role of HDAC6 as a transcriptional repressor in other cell types. Moreover, HDAC6 inhibition completely blocked TSA effects on HIF‐1 activity. HDAC6 associated with and deacetylated HSP90, an important cofactor for HIF‐1 function in NP cells, and HDAC6 inhibition decreased p300 transactivation in NP cells. Taken together, these results suggest that although multiple class I and class IIa HDACs control HIF‐1 stability, HDAC6, a class IIb HDAC, is a novel mediator of HIF‐1 activity in NP cells possibly through promoting action of critical HIF‐1 cofactors. © 2016 American Society for Bone and Mineral Research.